The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10608-021-10263-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting in the Face of Exclusion: Individuals with High Social Anxiety May Feel the Push of Social Pain, but not the Pull of Social Rewards

Abstract: Background Previous research has shown that high levels of trait social anxiety (SA) disrupt the social repair processes following a painful social exclusion, but the cognitive mechanisms involved in these processes and how trait SA may disrupt them remain unknown. Methods We conducted a preregistered study on Prolific participants ( N = 452) who were assigned to experience either social exclusion or inclusion and were then exposed to follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Furthermore, clinical examinations showed that individuals with SAD lacked motivation towards social rewards 108 . If the predicted reward value from a positive social outcome is substantially smaller compared to the potential social loss, individuals may choose avoidance behaviours 109,110 . Thus, our third factor (a pair) was altered social reward and loss processing, encoded in SocGain and SocLoss respectively.…”
Section: Model Construction Rationalementioning
confidence: 99%
“…Furthermore, clinical examinations showed that individuals with SAD lacked motivation towards social rewards 108 . If the predicted reward value from a positive social outcome is substantially smaller compared to the potential social loss, individuals may choose avoidance behaviours 109,110 . Thus, our third factor (a pair) was altered social reward and loss processing, encoded in SocGain and SocLoss respectively.…”
Section: Model Construction Rationalementioning
confidence: 99%
“…Fung and Alden [30] show that the intensity of social pain after the initial social exclusion could mediate the anxiety level of participants who experience subsequent social interaction. For individuals with higher social anxiety, their social repair is less than average social anxiety level individual after social exclusion, suggesting they might be less functional to release the negative effect of social pain, have a higher possibility to carry more weight of their past painful social event [31]. These effects could elevate and maintain the higher level of social anxiety and keep susceptible individuals more vulnerable within social situations.…”
Section: Higher Social Anxiety Inhibits the Need Repairmentioning
confidence: 99%
“…They tend to protect themselves by socially withdrawing [37]. Hudd [38] explained that the reaction of high social anxiety individuals might be because they are more sensitive to threats (e.g., excessive attention and responsivity to threat signals), and this overactive threat-avoidance motivation system could drive their behaviour within interpersonal situations. Besides, there are fewer rewards for high social anxiety individuals to reconnect to others.…”
Section: Higher Social Anxiety Inhibits the Need Repairmentioning
confidence: 99%
“…Evaluations on coping themes in pregnant women have concluded that quarantine has strengthened social support networks for pregnant women as the family members are at home and dedicate time and consideration to them, which has contributed to less threat-avoidance behaviors and thus moderately decelerated anxiety among pregnant women. On the contrary, with the lockdown policies in place, hampering pregnant women's access to essential obstetric care services accompanied by less involvement in social events has led to a significant decline in applying reward-seeking coping strategies and thus a substantial rise in major depression incurred [26,27].…”
Section: The Impact Of Engagement In Reward-seeking and Threat-avoida...mentioning
confidence: 99%